Strategic Agility in the AI Era: Examining the Role of Intelligent Business Systems - Ayush Gupta; Esmita Gupta (International Journal of Computer Information Systems and Industrial Management Applications, 2026)
With the continuous evolution of AI technology, businesses are increasingly leveraging its capabilities to make informed decisions about their strategies, adapting to significant market changes, and staying competitive in the ever-evolving digital landscape. In today’s world, strategic agility is more essential than ever as businesses have to make rapid decisions, modify business models and adapt to the trends in the conditions of the customer and competition. AI, machine learning, predictive analytics, automation, and real-time data processing enable intelligent business systems to deliver capabilities that can help today’s organizations bolster strategic responsiveness and organizational adaptability. In today’s business landscape, where artificial intelligence is a big player, this paper explores the significant role of intelligent business systems in attaining maximum strategic agility. It explores the possibility of AI based systems that can be flexible, innovative, reconfigure resources, scan the environment, and make real time decisions and respond to customers. Furthermore, the organizational barriers that affect the success of intelligent systems are discussed, including the technical readiness, employee competencies, support of top management, data quality, organizational culture and ethical governance. It’s about the human element and the need to strike a balance between AI recommendations and managerial choices; the risk of over-automation is a real possibility, and privacy, transparency, bias and accountability are issues. The paper takes a conceptual approach and discusses the latest research in the area and developments within AI in business management. They indicate that intelligent business systems, when complemented with organizational capabilities, and backed by proper governance, are more than just a technology to implement and use, they can be a strategic enabler. The study also suggests that those organizations that build strategic agility that is AI-informed, coupled with human expertise, organisational flexibility and a culture of continuous learning, are more likely to create sustainable strategic agility that may assist them in adapting to uncertainty in the evolving digital economy.